FOSTERING DIGITAL HEALTH IN PAKISTAN: AN INTERVENTIONAL STUDY REGARDING AWARENESS OF TELEMEDICINE AMONG PATIENTS OF DIVERSE HEALTHCARE SETUPS IN ISLAMABAD - Syed, Shehbano; Zaman, Minal; Anwar, Aiza; Hussain, Muhammad Junaid; Naeem, Muhammad Imad; Rizwan, Elyzae; Afzal, Asifa; Bilal, Arshia (Journal of Ayub Medical College Abbottabad, 2026)
ABSTRACT Introduction Telemedicine is the provision of healthcare services at a distance. With the rapidly increasing population in Pakistan and a chronic shortage of doctors in peri-urban and rural areas, telemedicine has become the need of the time. This research was conducted to create general awareness of telemedicine using video and assess the difference between pre-and post-interventional awareness with the aim of providing suggestions for making telemedicine more accessible and thus reducing the burden of the health care system. Methodology We conducted a pre and post-interventional study in various health care setups, on adults aged 18 and above who have been residents of Islamabad for over 6 months. Convenient sampling was done with a sample size of 98. Both pre-and post-interventional information was collected from the sample population through a self-developed questionnaire filled out through interviews. For intervention, an awareness session was conducted using a self-made video. Results Our pre & post-interventional grand mean scores were 6.89 and 9.48 respectively and this difference was highly significant statistically as p value was <0.001. The knowledge of telemedicine increased from 18 percent to 31.8 percent following the awareness session and 88 percent of people after learning about telemedicine services agreed that they were more accessible than looking for a doctor. Conclusion We conclude that the majority of the participants hold a favorable attitude toward telemedicine services. They have the means to access telemedicine but are unable to do so due to a lack of awareness; hence, there is a need for education and awareness through government-supported programs to encourage the utilization of telemedicine services. Keywords: Telemedicine, Awareness of telemedicine, Willingness to use Telemedicine